Insights into the effect of surface functional groups on catalytic performance for hydrogen generation from sodium borohydride. Issue 114 (1st December 2016) - Feng, Xiang; Song, Zhaoning; Guo, Tongtian; Yang, Rui; Liu, Yibin; Chen, Xiaobo; Yang, Chaohe
Abstract : The effect of surface functional groups on NaBH4 hydrolysis is elucidated using two Pt/polystyrene resin catalysts with –N(CH3 )3 OH or –SO3 H groups. Abstract : Sodium borohydride hydrolysis to generate hydrogen has great potential for mobile and portable applications, and designing efficient catalysts for this reaction is indispensable. In this work, the effect of surface functional groups on hydrogen generation rate (HGR) is investigated using two polystyrene resin supported Pt catalysts. The first type of resin (resin-NH) contains –N(CH3 )3 OH and abundant –OH groups, while the other one (resin-SH) contains –SO3 H and less –OH. After excluding the influences of basicity and Pt loading, it is found that the Pt/resin-NH catalyst exhibits a much higher HGR and lower activation energy compared with the Pt/resin-SH catalyst. Moreover, multiple techniques such as FT-IR, XRD, TEM and XPS are further employed to elucidate the intrinsic mechanism. Compared with the –SO3 H group, the –N(CH3 )3 OH and –OH groups not only facilitate Pt dispersion by enhancing metal–support interaction but also improve the electronic conductivity during hydrolysis by forming electron-enriched Pt active sites.